Association between travel time to delivery unit and unplanned out‐of‐hospital birth, infant morbidity and mortality: A population‐based cohort study. (5th May 2021) - Örtqvist, Anne K.; Haas, Jan; Ahlberg, Mia; Norman, Mikael; Stephansson, Olof
Abstract: Introduction: Over the last decade, a number of delivery units have been closed in Sweden, justified by both economic incentives and patient safety issues. However, concentrating births to larger delivery units naturally increases travel time for some parturient women, which may lead to unintended negative consequences. We aimed to investigate the association between travel time to delivery unit and unplanned out‐of‐hospital birth, and subsequent infant morbidity and mortality. Material and methods: We performed a population‐based cohort study including 365 604 women in the Swedish Pregnancy Register, giving birth between 2014 and 2017. Modified Poisson regression was used to investigate the association between travel time from home address to actual delivery unit, based on geographic information system analysis, and risk of an unplanned out‐of‐hospital birth. Analyses were stratified by parity and urban/rural residence. Lastly, the associations between an unplanned out‐of‐hospital birth and severe infant morbidity, stillbirth, peripartum, perinatal and neonatal mortality were investigated. Results: Of those with an unplanned out‐of‐hospital birth ( n = 2159), 65% had a travel time up to 30 minutes. A travel time between 31 and 60 minutes was associated with a doubled risk of unplanned out‐of‐hospital birth (adjusted risk ratio [RR] 1.96, 95% confidence interval [CI] 1.74–2.22) and women with a travel time of more than 1 hour had an adjusted RR of 3.19 (95% CI 2.64–3.86), compared with those with a travel time of <30 minutes. No difference in results was seen when stratified for parity and urban/rural residence. No association was found between unplanned out‐of‐hospital birth and severe infant morbidity. Significant associations were found in crude analyses for stillbirth (RR 1.85, 95% CI 1.09–3.13), peripartum (RR 1.93, 95% CI 1.18–3.16), perinatal (RR 2.03, 95% CI 1.28–3.23) and neonatal mortality (RR 3.08, 95% CI 1.27–7.46), although neonatal mortality was very rare (2.3/1000 out‐of‐hospital births). Similar effect estimates were found in the adjusted analyses, though no longer significant. Conclusions: Although the majority of unplanned out‐of‐hospital births occurred in the group of women with a travel time of 0–30 minutes, increasing travel time to a delivery unit is associated with unplanned out‐of‐hospital birth, which may increase the risk of mortality.